1980
DOI: 10.1111/j.1476-5381.1980.tb07044.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thyrotrophin‐releasing Hormone, and Methionine‐enkephalin on Gastric Acid and Pepsin Secretion in the Cat

Abstract: upon Tyne NEI 7RU1 The effect of intravenous administration of thyrotrophin-releasing hormone (TRH) and methionine-enkephalin on gastric acid and pepsin secretions was investigated in conscious cats prepared with chronic gastric fistulae.2 TRH, 20 jig kg-' h-', did not influence unstimulated gastric acid secretion, nor gastric acid secretion stimulated by submaximal doses of pentagastrin or histamine. Pepsin secretion stimulated by pentagastrin was not influenced by TRH. 3 TRH, 20 pg kg-' h-, significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1981
1981
1984
1984

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…27], and man [2,17], In contrast, stimu latory effects occurred in the dog [10; these workers also reported inhibition] and man [6,19]. Finally, Gascoigne et al [8] found no influence of opioids on gastric acid secretion in the cat in vivo, and Canfield and Spencer [3] observed no effect in the isolated stomach of rats.…”
Section: Introductionmentioning
confidence: 91%
“…27], and man [2,17], In contrast, stimu latory effects occurred in the dog [10; these workers also reported inhibition] and man [6,19]. Finally, Gascoigne et al [8] found no influence of opioids on gastric acid secretion in the cat in vivo, and Canfield and Spencer [3] observed no effect in the isolated stomach of rats.…”
Section: Introductionmentioning
confidence: 91%
“…It is still a matter of debate whether opioids have an effect on gastric acid secre tion and if so, whether they stimulate or inhibit, and whether the effect is elicited in the gastric mucosa or centrally [3,4,6,8,9,11,12,14,17,21,23], In a previous paper [10], we have demonstrated for the first time that the opioid peptide D-ala2-Z)-leu5-enkephalin (DADLE) [25] enhanced acid secre tion stimulated by histamine in isolated and enriched guinea pig parietal cells. The effect was blocked by the competitive opioid antag onist naloxone, suggesting a specific effect on opioid receptors.…”
Section: Introductionmentioning
confidence: 99%